(untitled) (Altre Modernità, 2013)
La destrucción de todas las cosas (1992) by Hugo Hiriart belongs to a group of apocalyptic works of fiction easily detectable in the Mexican literary production between the Twentieth and Twenty-First Centuries. This paper aims at highlighting how the novel, describing the tragic end of the Mexican Civilization caused by an alien attack, blends together science fiction elements with references to the Spanish Conquest and its main events and characters, often adopting ? in a new perspective ? the stylistics and writing techniques of the Sixteenth-Century chronicles. Further objective of the paper is to analyze Hiriart’s reflections on the present and past condition of Mexico, which show the collapse of the revolutionary dream with irony and dark humor, and identify the decline of values in its political and cultural context as a cause of the new destruction of Mexico City.